Determinación de alteraciones morfológicas de células sanguíneas en personas expuestas a la contaminación laboral por Pb y Hg en trabajadores de la mina Cristo De Oro des sitio Muyuyacu, cantón Ponce Enríquez, provincia del Azuay, 2013. - Pesantes Yadaicela, Kerly Vanessa (2015)
the present research had as main objective of determine the morphological alterations of blood cells as biological indicators of lead poisoning and mercury in workers Cristo de Oro site Muyuyacu Canton Ponce Enriquez a Mid 2015 mine, as the mining sector an area of high labor pollution. The variables were the concentration determined hematocrit hemoglobin, erythrocytes constant corpuscular and blood cell abnormalities.